Public Expenditure Policies in Southeast Europe - World Bank (Washington, DC, 2012)
The countries of Southeastern Europe (SEE) and the province of Kosovo (thereafter, Kosovo) have undergone a significant, though difficult, transition over the past decade. Series of conflicts in the region have complicated the transition process, which in the initial phase focused on macroeconomic stabilization and reconstruction. Helped by macroeconomic stability and efforts in advancing structural reforms, real Gross Domestic Product, or GDP growth in region has picked up this century, averaging 5.8 percent during 2000-2006, although it has still lagged the pace in both the more advanced reformers and the average for emerging Asia. In addition to boosting living standards, the SEE countries' shared aspiration to advance European Union (EU) integration has been increasingly shaping the reform agenda. This report reviews the level, composition and outcomes of government spending and distills some of the lessons that emerge from efforts by the SEE countries in reforming expenditure policies. The report identifies key remaining challenges and proposes a broad menu of options in further reforms of sectors that account for the largest shares of public spending across the countries, and where reforms are likely to have significant budgetary implications. This has motivated the choice of sectors discussed in the report: social protection (including pensions), health, education, public administration and infrastructure.